Peranan BK Dengan Menggunakan Teknik Modelling Dalam Mencapai Tugas Perkembangan AUD Di Kelas Raudhah I Ra As-Sa’adah - Mardianto, Mardianto; Sikumbang, Ahmad Tamrin; Hadrah, Hadrah (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
The problem in this research is the role of guidance and counseling using modelling techniques in achieving early childhood development tasks in the Raudhah I RA As-Sa’adah class. This study aims to explain the role of counseling guidance, the use of modelling techniques, and the role of guidance and counseling using modelling techniques in achieving development tasks in Raudhah I RA As-Sa’adah class. This research was conducted using qualitative research using descriptive methods. The subjects of this study were students. The informants are the Principal, Treasurer, Class Teachers and Parents. Data collection techniques in this study through: Observation, Interview dan Documentation. The data analysis process was carried out by: Data reduction, Data presentation and Conclusion drawing. Then the data collected is checked the validity of the data through data triangulation. General findings in this study are the task of early childhood development. The results of the research are: (1) The role of guidance an counseling and counseling which is very important in RA As-Sa’adah (2) The use of modelling techniques is carried out well (3) The role of guidance and counseling using modelling techniques in achieving early childhood development tasks has not yet been implemented optimal